From #feesmustfall to #futuresmustrise: The evolution of student activism and policy change at Mangosuthu University of Technology. A qualitative case study. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Student activism has been a pivotal force in shaping higher education in South Africa. At Mangosuthu University of Technology (MUT), the #FeesMustFall movement (2015–2017) spurred demands for free education, decolonized curricula, and institutional reform. While immediate outcomes of the protests are well documented, limited attention has been paid to the long-term evolution of activism into structured policy engagement during the emerging “FuturesMustRise” era. Methods This qualitative case study was conducted at MUT between January 2024 and April 2025. Data were collected through semi-structured interviews with 15 former and current student leaders active from 2015 to 2025, and 5 university administrators involved in governance and transformation. In addition, 20 institutional documents, including protest memoranda, council minutes, policy revisions, and transformation reports, were analysed. Braun and Clarke’s thematic analysis framework was applied to ensure triangulation and depth. Results Findings revealed a post-2018 shift from protest to structured activism, with 80% of student leaders participating in governance structures such as the Transformation Committee and SRC Policy Forums. Administrators (60%) acknowledged activism’s influence on reforms in financial aid and student accommodation. However, only 27% of participants (both students and administrators) viewed curriculum decolonization efforts as meaningful, with the majority describing such initiatives as symbolic or superficial. A decline in sustained activism following partial victories was also noted, risking stagnation of deeper reforms. Conclusion Student activism at MUT has transitioned into formal governance engagement, resulting in incremental but meaningful policy change. Yet, challenges remain in achieving comprehensive transformation, particularly in decolonizing the curriculum. Recommendations MUT should institutionalize student advisory structures with decision-making authority, implement leadership development initiatives, and create transparent systems for tracking reforms. Above all, curriculum decolonization must be prioritized beyond symbolism to achieve long-term institutional change.